Subchondral Bone Remodeling: A Therapeutic Target for Osteoarthritis - Zhu, Xiaobo; Chan, Yau Tsz; Yung, Patrick S. H.; Tuan, Rocky S.; Jiang, Yangzi (Frontiers in Cell and Developmental Biology, 2021)
There is emerging awareness that subchondral bone remodeling plays an important role in the development of osteoarthritis (OA). This review presents recent investigations on the cellular and molecular mechanism of subchondral bone remodeling, and summarizes the current interventions and potential therapeutic targets related to OA subchondral bone remodeling. The first part of this review covers key cells and molecular mediators involved in subchondral bone remodeling (osteoclasts, osteoblasts, osteocytes, bone extracellular matrix, vascularization, nerve innervation, and related signaling pathways). The second part of this review describes candidate treatments for OA subchondral bone remodeling, including the use of bone-acting reagents and the application of regenerative therapies. Currently available clinical OA therapies and known responses in subchondral bone remodeling are summarized as a basis for the investigation of potential therapeutic mediators.